Fleet Control With IoT Using TLS Certificates And SIM7000G GPS Device - René Cruz Guerrero; José Epifanio Rojas-Cortés; German Cuaya-Simbro; Isaías Simón-Marmolejo (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Companies that apply technology to monitor mobile units face several challenges such as obtaining the best precision in geolocation coordinates, having good communication quality and security in data transmission, detecting route deviations, avoiding delays in their journeys, among others. This article proposes a real-time transport fleet monitoring system that uses the Internet of Things (IoT) to contribute to some of these challenges and improve the overall user experience of the collected data. A model is presented that includes a proposal to reinforce security in data transit with MQTT using Transport Layer Security (TLS) and a study carried out with the purpose of detecting which GPS coordinate acquisition device is more precise. 368 tests were carried out in five different coordinates with SIM800, ESP32, SIM7000G considering altitude, latitude, longitude, speed, number of satellites and sending time. The device that provided the best results in coordinate accuracy was the SIM7000G, even meeting the requirements for battery life and storage capacity due to the demand required to execute TLS security certificates.